2012
DOI: 10.1111/j.1443-1661.2012.01309.x
|View full text |Cite
|
Sign up to set email alerts
|

Is it proper to use non‐magnified narrow‐band imaging for esophageal neoplasia screening? Japanese single‐center, prospective study

Abstract: In both HD and non-HD endoscopy, NBI is less likely than WLI to miss a lesion. Even with non-HD endoscopy, NBI is suitable for esophageal standard examinations in general hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…Two did not provide complete data to calculate sensitivity, specificity, and accuracy values in either the per-patient or per-lesion analysis [7, 20]. In one, the examinations were performed by inexperienced endoscopists [8]; and in another, the data were collected retrospectively [21]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two did not provide complete data to calculate sensitivity, specificity, and accuracy values in either the per-patient or per-lesion analysis [7, 20]. In one, the examinations were performed by inexperienced endoscopists [8]; and in another, the data were collected retrospectively [21]. …”
Section: Resultsmentioning
confidence: 99%
“…For experienced endoscopists, sensitivity levels were consistent between the two methods [7]. Yokoyama et al showed that NBI without magnification is suitable for esophageal assessment when searching for a neoplasm in a high-risk population, even without high-definition imagery [8]. …”
Section: Introductionmentioning
confidence: 98%
“…Multiple prospective studies have shown that nonmagnified NBI examination is superior to WLI in detection of early esophageal lesions for screening of high-risk patients (10)(11)(12)(13) (15). In addition, NBI endoscopy also had a higher specificity comparing to Lugol chromoendoscopy (per lesion analysis 82% vs. 37%).…”
Section: Review Articlementioning
confidence: 99%
“…Studies using HD endoscopy failed to show a significant benefit for additional chromoendoscopy (real or virtually) in the detection of dysplasia in squamous cell carcinoma and Barrett's oesophagus [26,27,28,29]. The current ESGE guideline does not classify the white light endoscopy (SD) as sufficiently exact in differentiating and diagnosing pre-neoplasm conditions and lesions ( Helicobacter pylori (HP) gastritis, atrophic gastritis, intestinal metaplasia); thus, the use of the best available endoscopy technique and the collection of sampling biopsies in the endoscopic monitoring are requested for patients with a precancerous condition ([3] chapter 4.1; [30]).…”
Section: Quality Indicators/parameters For Specific Proceduresmentioning
confidence: 99%